2002
DOI: 10.1016/s0167-8809(02)00005-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions from a New Zealand cropped soil: tillage effects, spatial and seasonal variability

Abstract: Agricultural practices are believed to be the major anthropogenic source of enhanced nitrous oxide (N 2 O) gas emissions in New Zealand. Studies conducted in New Zealand generally suggest low N 2 O emission from pasture; however, there is little information for arable farming systems. This paper evaluates tillage and land use effects on N 2 O emissions using a closed chamber technique at an Ohakea silt loam (Gleyic luvisol) where winter oats (Avena sativa L.)/fodder maize (Zea mays L.) was double-cropped for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 26 publications
2
60
0
5
Order By: Relevance
“…Another model, NCGAS, predicted higher emissions from no-till situations with a stronger effect in drier environments (Mummey et al 1998). In comparative field studies, N 2 O emissions under no-till were greater than (Aulakh et al 1984;MacKenzie et al 1998;Ball et al 1999;Baggs et al 2003;Yamulki and Jarvis 2002;Koga et al 2004), smaller than (Jacinthe and Dick 1997;Kessavalou et al 1998;Lemke et al 1999;Kaharabata et al 2003;Del Grosso et al 2005) and approximately equal to (Lemke et al 1999;Robertson et al 2000;Choudhary et al 2002;Kaharabata et al 2003) emissions from tilled soils. Contrasting effects of no-till on N 2 O fluxes have also been observed depending on the N fertilizer type that was applied (Venterea et al 2005).…”
Section: Determination Of Efecomentioning
confidence: 90%
“…Another model, NCGAS, predicted higher emissions from no-till situations with a stronger effect in drier environments (Mummey et al 1998). In comparative field studies, N 2 O emissions under no-till were greater than (Aulakh et al 1984;MacKenzie et al 1998;Ball et al 1999;Baggs et al 2003;Yamulki and Jarvis 2002;Koga et al 2004), smaller than (Jacinthe and Dick 1997;Kessavalou et al 1998;Lemke et al 1999;Kaharabata et al 2003;Del Grosso et al 2005) and approximately equal to (Lemke et al 1999;Robertson et al 2000;Choudhary et al 2002;Kaharabata et al 2003) emissions from tilled soils. Contrasting effects of no-till on N 2 O fluxes have also been observed depending on the N fertilizer type that was applied (Venterea et al 2005).…”
Section: Determination Of Efecomentioning
confidence: 90%
“…Other studies have found no significant effect of tillage on N 2 O production from soybean crops (Parkin and Kaspar 2006;Jantalia et al 2008). Results from previous studies on the effects of tillage on soil N 2 O production are thus contradictory (Ball et al 1999;Choudhary et al 2002). A review article by Rochette (2008) concluded that a notillage treatment increased N 2 O emissions in poorly-aerated soils, whereas the same treatment resulted in the decrease in N 2 O emissions in well-aerated soils.…”
Section: Tillagementioning
confidence: 99%
“…N 2 O fluxes are believed to be driven primarily by the availability of nitrogen compounds in the soils (ammonium and nitrate) (Davidson et al, 2000) as well as physical properties of the soil such as WFPS, aerobic extent, soil type, temperature and compaction (Ball et al, 2008;ButterbachBahl et al, 2013;Choudhary et al, 2002;Davidson et al, 2000;Turner et al, 2008). The collection of these data on a temporal/spatial scale which would allow these models to be applied is not often logistically possible or affordable.…”
Section: Gap Filling Of N 2 O Fluxesmentioning
confidence: 99%
“…Chatskikh and Olesen, 2007;Merbold et al, 2014;Omonode et al, 2011;Pinto et al, 2004;Yamulki and Jarvis, 2002), whereas others have shown a zero (i.e. Boeckx et al, 2011;Choudhary et al, 2002) or potentially negative effect of tillage (−0.88 kg N ha −1 ; Tan et al, 2009). There is little consensus among these studies on the relative effect of different drivers of N 2 O production.…”
Section: Introductionmentioning
confidence: 99%